Blessings: Layers of Meaning in Sacred Visual Language - Tsappa, Lilian (My University, 2021)
A recurrent element in Christian Orthodox iconography is the depiction of “Blessings”: two distinct types of hand and finger gestures performed by the Hand of God, by Jesus Christ, and other sacred personages. The authoritative iconographic scholarship provides no satisfactory exegesis as to the origin, meaning or liturgical use of these sacred gestures that are unique examples of God - Man’s visual and body language. This work aims to shed light into this intriguing subject by examining the Blessings’ possible ties to mystical Christianity, and, in view of their commonality, to sacred hand gestures (mudras) depicted in the religious iconography and philosophical traditions of the East, which deem them to be transformational experiences.